Visual climate change art 2005–2015: discourse and practice. (3rd June 2016) - Nurmis, Joanna
Abstract : During the last decade (2005–2015), artists from all over the world have taken on climate change as the subject matter of their work. Encouraged by activists (most notably Bill McKibben), artists have appropriated climate change as a social problem and decided that they too, alongside journalists, scientists, and activists, were called upon to engage with this issue. Dozens of noteworthy exhibitions, most notably in Boulder (2007), London and Copenhagen (2009), Paris (2012), New York (2013), Boston (2014), and Melbourne (2015), have placed climate change art on the map as a new and timely genre, displaying relevant artworks both alongside climate negotiations and in dedicated gallery spaces such as the Barbican in London. I argue that much progress has been made in appropriating climate change art as an essentially artistic, rather than propagandistic or activist practice. Although caught in the net of many criticisms, climate change art plays a crucial role in allowing the public to rethink the role of human beings' everyday activities in irrevocably altering the climate system. In effect, climate change art makes the Anthropocene a cultural reality. However, the review points out a strong artistic trend toward the imagery of apocalyptic sublime, which results in art that may be poignant, but falls out of step with the self‐professed motivations of artists and curators alike. WIREs Clim Change 2016, 7:501–516. doi: 10.1002/wcc.400 This article is categorized under: Trans‐Disciplinary Perspectives > Humanities and the Creative Arts